Work From Home On Software Engineer Productivity Analysis: A Case Study Of Batam City - Steven Salim; Tony Wibowo (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
The COVID-19 pandemic has shaken all people in the world and affected all aspects of modern human life. Seeing that there has been a very significant increase in the speed of the spread of the virus, the government is taking part in suppressing the rate of the spread of the plague, one of the ways is by making a remote work policy, or better known as Work From Home (WFH). All companies regardless of business process comply with this regulation. This study uses qualitative and quantitative data comparison analysis methods from interviews and distributing questionnaires conducted to software engineers in the city of Batam regarding their productivity comparison between WFO and WFH during post-pandemic. We used means comparison analysis and SPSS to help analyze the data. The results showed that in the physical workplace environment factors, work-life balance, work flexibility, and collaboration and communication did not have a significant effect from WFH activities on the performance of the software engineer himself. Software engineering and computer-related occupation generally can perform the generally the same productivity regardless of the place of work. Further studies should be done to explore this furthermore.